1997
DOI: 10.1148/radiology.203.3.9169707
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma: role of whole-body 2-deoxy-2-[F-18]fluoro-D-glucose (FDG) PET in nodal staging.

Abstract: FDG PET may be more accurate for detecting nodal lymphoma than incremental CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
104
0
13

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(124 citation statements)
references
References 0 publications
7
104
0
13
Order By: Relevance
“…However, it is cumbersome to perform and insensitive for detecting residual disease. Recently, several studies showed that FDG PET can be an alternative tool to overcome these limitations of anatomic imaging and Ga-67 scans in malignant lymphomas (22)(23)(24)(25)(26)(27)(28)(29)(30). These data, however, have been obtained with dedicated PET cameras.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is cumbersome to perform and insensitive for detecting residual disease. Recently, several studies showed that FDG PET can be an alternative tool to overcome these limitations of anatomic imaging and Ga-67 scans in malignant lymphomas (22)(23)(24)(25)(26)(27)(28)(29)(30). These data, however, have been obtained with dedicated PET cameras.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to extranodal involvement, CoDe PET detected four more lesions than did CT-MRI and it missed no lesion. Many reports have appeared on the use of FDG PET to stage malignant lymphoma (22)(23)(24)(25)(26)(27)(28), and they show that FDG PET is more accurate than CT. Moog et al (24,26) showed that FDG PET is more accurate for detecting nodal lesions and extranodal lymphomas in primary staging than is CT. In our study, however, the results of CoDe PET showed a low sensitivity rate compared with CT-MRI in nodal detection, but CoDe PET was more sensitive than CT-MRI in identifying extranodal involvement in the small number of cases evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very important to have a good evaluation tool. 18F-FDG PET/CT has a growing interest for staging (8) and to evaluate the therapeutic response in lymphomas (9; 10). In our patients the initial evaluation by 18F-FDG PET/CT allows to establish the primary sinuses localisation of the lymphoma.…”
Section: Questionmentioning
confidence: 99%
“…Preliminary data suggest that FDG-PET is a useful tool to stage and monitor lymphoma. [13][14][15][16][17][18][19][20][21][22][23] However, there has been scarce data comparing FDG-PET and Ga-67 scintigraphy; thus, their comparative value is still conjectural. 13,24,25 Accordingly, we prospectively compared the accuracy of whole-body FDG-PET and Ga-67 scintigraphy to identify disease sites in HD and non-Hodgkin lymphoma (NHL; intermediate grade and high grade) at initial staging or recurrence before chemotherapy.…”
mentioning
confidence: 99%